Pertumbuhan Bibit Acacia crassicarpa dengan Pemberian Bokashi dari Beberapa Bahan Utama - Ali Martinus (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2017)
Martinus et al, 2017. Acacia crassicarpa Seedling Growth with Bokashi from Variety Ingredient. JLSO 6(2):185-191.The provision of nutrients for plants in HTI (Plantations Industries), especially at the time of seeding, can be done with the addition of organic and inorganic fertilizers. Inorganic fertilizers can provide nutrients quickly. However, if this is done continuously will cause the soil damages. Meanwhile, although organic fertilizers provide slow nutrient, it can be improve physical and chemical soil. One kind of organic fertilizer is Bokashi., Bokashi compost is produced from the fermentation process. This study aims to determine the effect of variety ingredient of Bokashi as nursery media makers onÂ  A.crassicarpa seedling growth. This trial uses design complete randomized design (RCD), with four replications and 7 treatments. Treatments include (A) NPK, (B) Kumpai, (C) Desmodium, (D) Salvinia (E) A. Crassicarpa, (F) A. Mangium, (G) E. pellita. The experimental results showed that the main ingredient kiambang bakashi giving a better effect on the growth of A. crassicarpa in the nursery than kumpai, Desmodium, leaf litter A. mangium, A. crassicarpa, E. pellita and control (NPK).